Clinical-epidemiological profile and trends in the treatment of fungal keratitis in an ophthalmological institute in northern Peru. A 10-year study - Chirinos-Saldaña, Patricia (2024)
Purpose: To characterize the epidemiological and clinical profile of fungal keratitis (FK) and analyze the success rates of its treatment modalities during the decade 2009-2018 at the Regional Institute of Ophthalmology of Trujillo, Peru. Materials and Methods: Retrospective and descriptive study of data extracted from medical records of patients with FK. Variables such as demographic, clinical, microbiological, risk factors, treatment modalities, and complications were studied. Annual and overall success rates of medical treatment (MT) and first and second-line surgical treatment (ST) were calculated. Results: 345 patients were studied, with a mean age of 44.4 +/- 16.6 years, of whom 75.4% were males. 90.4% reported one or more risk factors, with ocular trauma being the most frequent (81.2%). Ulcers were predominantly central (61.5%). Culture positivity was 35.8%, with filamentous fungi isolated in 92.3% of cases. MT was the preferred treatment modality, and its use increased annually. The overall success rates of MT, first-line ST, and second-line ST were 59.2%, 68.6%, and 65.1%, respectively. After MT and ST, visual acuities > 20/60 were achieved in 43.3% and 8.8% of cases, respectively. Conclusions: FK predominated in young adult males with a history of ocular trauma. Corneal ulcers mainly affected the visual axis. Culture positivity was low, with filamentous fungi isolated in most cases. The success of ST was higher than that of MT, although resulting in worse visual acuities.